EARLY LARVAL DEVELOPMENT OF CARIDINA SP. (CRUSTACEA, DECAPODA, ATYIDAE) - Lakshmi, S (Indian Journal of Fisheries, 2011)
The early larval development of Caridina sp. collected from the low-salineinshore waters of Cochin is described. The larvae hatch out in relatively advancedstage and pass through 5 moults during a period of 11 days, under laboratoryconditions. Rearing iexperiments were carried out in the medium with salinity,16-17%. and at temperature, 28.0Â°C to 28.5Â°C. IDescriptions of the adultshrimp and the first three zoeal stages are given with illustrations. A comparisonof the eariy larval development of Caridina sp, with that of the allied species ismade.